Analysis of 30 years’ historical climate change trends and variability in Mt. Elgon, Kenya, Africa (Journal of Sustainability, Environment and Peace, 2023)
Mountain habitats are critical for identifying the effects of climate change on livelihoods. The study's main goal was the “analysis of 30 years’ historical climate change trends and variability in Mt. Elgon, Kenya, Africa.” The study employed primary data from KIIs, FGDs, and household questionnaire survey representing community views. The study also employed secondary data from the Kitale Meteorological Station (KMS) for rainfall and temperature from 1986 to 2015. Statistical and descriptive techniques were used to analyse both quantitative and qualitative data. The yearly rainfall trend has typically been growing increasing as evidenced by the positive slope of 9.96, but with a tiny coefficient of determination of 0.28, according to the study of rainfall data. Within time series, MAM trends have been dropping, whilst OND trends have been increasing. However, when these trends were tested for significance using linear regression, the p-values were found to be bigger than the level of confidence, indicating that the increases in trends are not significant (5 percent). According to the study's findings, temperature trends have risen significantly between 1986 and 2015. The temperature trend had a significance of 5%, which is comparable to climate change as a result of global warming. Over 90% of the farmers polled said they had noticed changes in climate patterns as far back as 30 years. As a result, the region's overlapping climate changes include altered precipitation regimes and higher surface temperatures. These findings are crucial for improving adaptive ability and increasing resilience, as well as making informed decisions and planning future livelihood management strategies. This data can also be used to develop appropriate response mechanisms to adapt and mitigate the effects of climate change and variability on livelihoods in the study area.
Keywords: Mountain ecosystems, climate change, climate variability, response mechanisms.